2005
DOI: 10.1177/1063293x05050910
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support System for Selecting Collaborative Product Development Partners

Abstract: Collaboration is becoming a new current paradigm for product manufacturing, as computer networks facilitate collaboration with partners located in widely distributed locations. Computer network technologies allow a large number of candidate partners to be examined for possible collaboration, so that the most suitable partner, or partners, can be selected from a broader, more diverse group than previously possible. In order to take best advantage of the collaboration paradigm, the precise method for selecting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Recent developments in partner selection generally focus on the supply chain management aspect of product development [3][4][5][6][7][8][9][10][11]. However, this study found that no effective and practical approach/method is available for selecting cooperative enterprises based on the characteristics of ACE.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent developments in partner selection generally focus on the supply chain management aspect of product development [3][4][5][6][7][8][9][10][11]. However, this study found that no effective and practical approach/method is available for selecting cooperative enterprises based on the characteristics of ACE.…”
Section: Introductionmentioning
confidence: 91%
“…Establish the decision matrix (R) Equations ( 9) and ( 10) are used to normalize the quantification numbers for the five collaborative enterprises. The decision matrix is then established via Equation (11), as shown in Table 37. Step 11.…”
Section: Illustrative Examplementioning
confidence: 99%
“…an external scan and an internal assessment, to the identified potential partners during market research and . evaluate alternatives according to competencies using decision analysis (Yoshimura et al 2005, Hacklin et al 2006. A more detailed evaluation is conducted through decision analysis, following a general assessment offered by SWOT.…”
Section: Effective Partnership Processmentioning
confidence: 99%
“…Piloting innovative projects and New Product Development Processes (NPDP) is a major concern for top management [1]. Increased attention is directed toward time to market and cycle time reduction as a way for firms to build and strengthen their competitive advantage [2,3].…”
Section: Introductionmentioning
confidence: 99%